2020
DOI: 10.1186/s12885-020-07287-1
|View full text |Cite
|
Sign up to set email alerts
|

WDHD1 facilitates G1 checkpoint abrogation in HPV E7 expressing cells by modulating GCN5

Abstract: Background: Genomic instability is a hallmark of cancer. The G1 checkpoint allows cells to repair damaged DNA that may lead to genomic instability. The high-risk human papillomavirus (HPV) E7 gene can abrogate the G1 checkpoint, yet the mechanism is still not fully understood. Our recent study showed that WDHD1 (WD repeat and high mobility group [HMG]-box DNA-binding protein 1) plays a role in regulating G1 checkpoint of E7 expressing cells. In this study, we explored the mechanism by which WDHD1 regulates G1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…Recent studies have observed the overexpression of WDHD1 in the great majority of lung cancers and esophageal squamous cell carcinomas ( Sato et al, 2010 ). WDHD1 has also been reported to facilitate the abrogation of G1 checkpoint upon DNA damage, leading to genomic instability and eventually tumorigenesis ( Zhou et al, 2020 ). Moreover, WDHD1 could accelerate cell proliferation, cell viability, and metastasis in several cancers including cholangiocarcinoma and breast cancer ( Sato et al, 2010 ; Liu et al, 2019 ; Ertay et al, 2020 ; Zhou and Chen, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have observed the overexpression of WDHD1 in the great majority of lung cancers and esophageal squamous cell carcinomas ( Sato et al, 2010 ). WDHD1 has also been reported to facilitate the abrogation of G1 checkpoint upon DNA damage, leading to genomic instability and eventually tumorigenesis ( Zhou et al, 2020 ). Moreover, WDHD1 could accelerate cell proliferation, cell viability, and metastasis in several cancers including cholangiocarcinoma and breast cancer ( Sato et al, 2010 ; Liu et al, 2019 ; Ertay et al, 2020 ; Zhou and Chen, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, research on the mechanism of WDHD1 in cancer has not been extensive. Several studies have linked the WDHD1 gene to key processes such as tumorigenesis and metastasis [ 18 , 63 , 64 ]. For example, Li et al proposed that WDHD1 could regulate the stability of the GCN5 protein and the acetylation of histone H3 with remarkable precision, which might play an important role in tumor cell growth [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the notion that STAT3 regulates WDHD1 transcription and therefor promotes DNA replication. Interestingly, both STAT3 and WDHD1 have been implicated in cell cycle checkpoint control, epithelial-mesenchymal transition, tumor growth and metastasis [36,37,48,49] and reviewed in [50,51]. It would be interesting to examine whether STAT3 performs these functions through WDHD1.…”
Section: Discussionmentioning
confidence: 99%